Pengaruh E-Service Quality Dan Kepuasan Terhadap Loyalitas Konsumen Lazada Melalui Kepercayaan Sebagai Variabel Intervening Pada Mahasiswa Universitas Negeri Padang - Kanda Juanda; Rino Rino (Universitas Negeri Padang, 2023)
This study was conducted to examine Lazada's consumer loyalty to Padang State University students who were influenced by e-service quality and satisfaction and enhanced by trust as an intervening variable. Causative is the type of research chosen by the researcher. The research technique was chosen by purposive sampling with a total sample of 140 based on SEM. Primary data is the data used in this study, the data obtained from distributing questionnaires to undergraduate students at the University of Padang with the criteria of having made a purchase at the online store at Lazada and had made repeated purchases at the online store at Lazada. The analytical method used is SEM analysis using SmartPLS 3.0 software. The results obtained are: 1) Lazada consumer loyalty is significantly affected by e-service quality, 2) satisfaction is significantly influenced by e-service quality, 3) Lazada consumer loyalty is significantly influenced by satisfaction, 4) trust is significantly affected influenced by the quality of e-service, 5) trust is significantly influenced by satisfaction, 6) consumer loyalty is significantly influenced by trust, 7) Lazada consumer loyalty is significantly influenced by the quality of electronic services through trust, 8) Lazada consumer loyalty is significantly influenced by satisfaction through trust.